PENGGUNAAN METODE PEMBELAJARAN ROLE PLAYING UNTUK MENINGKATAN MINAT BELAJAR MATEMATIKA PESERTA DIDIK - Herlindya Herlindya; Sutirna Sutirna (Universitas Bina Bangsa, 2022)
This writing aims to examine the use of the Role Playing learning method in an effort to increase interest in learning mathematics. In this article, the author uses a qualitative descriptive method, using a literature review/literature study approach by collecting information relevant to the topic or problem being researched. This is attempted to obtain an overview of the use of the Role Playing learning method in an effort to increase interest in learning mathematics. Where if the interest in learning mathematics is great, it tends to result in the achievement of learning and high learning achievement. So, in this paper, it is explained how the use of the Role Playing learning method is to increase interest in learning mathematics